(untitled) (Research, Society and Development, 2021)
Introduction: Chest trauma consists of a physical shock with a strong impact that causes damage of varying extent in the body. Objective: To assess the epidemiological profile and survival of chest trauma victims, associated or not with polytrauma, using the TRISS and TRISS-like severity indexes. Methods: Observational, prospective, quantitative study of thoracic trauma victims who entered the emergency department of a hospital in the state of Sergipe. An instrument with physiological and sociodemographic data about topography and clinical information was used. Mann Withney, Fisher, Pearson’s Chi-square, Pearson’s Chi-square tests with Monte-Carlo simulations were used, considering significant when p<0.005. Results: From the sample of 101 patients, a median age of 32 years was obtained, with 84,2% being male and 15,8% being female, which 47,5% suffered a transport accident, with small difference between blunt mechanism (51.5%) and penetrating mechanism (48,5%). Most accidents had pre-hospital care (90,1%), 34,7% died and 44% needed support in intensive care unit. The average survival probability of traumatized was 98,4%. Victims assessed by TRISS-like had a 98,7% probability of survival, while those on TRISS had 98,4%. Conclusion: It was found that the predominant cause of chest trauma was a transport accident with equivalent blunt and penetrating mechanisms, which the epidemiological profile was men, adults aged between 30 and 44 years. Although most of them received pre-hospital care, the death rate was considerable.